The Institutional Role Of Village-Owned Enterprises In Enhancing Community Economic Development: A Case Study Of Kampung Bumi Ajo, Moswaren District, South Sorong Regency (International Journal of Environmental Sciences, 2025)
Village-Owned Enterprises (BUMDes) serve as strategic instruments in realizing the economic independence of rural communities in Indonesia. This study aims to analyze the institutional capacity of BUMDes Tabam Rait Mos in promoting economic development in Kampung Bumi Ajo, Moswaren District, South Sorong Regency. Employing a qualitative descriptive method, the research adopts the institutional theory framework proposed by Scott (2001), which consists of three analytical pillars: regulatory, normative, and cognitive. Data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that while the regulatory dimension is relatively established through formal village regulations, there remains a gap in the normative and cognitive dimensions. Community engagement and shared understanding regarding the function of BUMDes are still limited. The study concludes that strengthening the institutional pillars holistically is essential to improve the performance and sustainability of BUMDes as a driver of local economic transformation.